Quantitatively Monitoring In Situ Mitochondrial Thermal Dynamics by Upconversion Nanoparticles - Di, Xiangjun (Nano Lett, 2021)
[Image: see text] Temperature dynamics reflect the physiological conditions of cells and organisms. Mitochondria regulate the temperature dynamics in living cells as they oxidize the respiratory substrates and synthesize ATP, with heat being released as a byproduct of active metabolism. Here, we report an upconversion nanoparticle-based thermometer that allows the in situ thermal dynamics monitoring of mitochondria in living cells. We demonstrate that the upconversion nanothermometers can efficiently target mitochondria, and the temperature-responsive feature is independent of probe concentration and medium conditions. The relative sensing sensitivity of 3.2% K(–1) in HeLa cells allows us to measure the mitochondrial temperature difference through the stimulations of high glucose, lipid, Ca(2+) shock, and the inhibitor of oxidative phosphorylation. Moreover, cells display distinct response time and thermodynamic profiles under different stimulations, which highlight the potential applications of this thermometer to study in situ vital processes related to mitochondrial metabolism pathways and interactions between organelles.